PENGARUH KEMAMPUAN MANAJERIAL, KOMUNIKASI DAN STRES TERHADAP KOMITMEN ORGANISASI DI KEPOLISIAN RESORT LEBAK - Ali Maghfur; Ade Jaya Sutisna; Yumhi Yumhi (E-Journal Studia Manajemen, 2020)
This study aims to obtain information related to the possibility of whether organizational commitment is influenced by managerial ability, communication and stress. Using a causal study through a survey at the Police Resort Lebak Polda Banten, Indonesia, for a sample of 85 personnel, data for each variable was collected separately by respondents who filled out the questionnaire. The method used in this research is quantitative survey method, while the analysis technique used is path analysis using correlation and regression.The results prove that there is an influence of managerial ability on organizational commitment, there is an influence of communication on organizational commitment, there is an effect of stress on organizational commitment, and there is an influence of managerial ability, communication and stress together on organizational commitment.These findings indicate that organizations need to consider the variables of organizational culture, discipline, and work motivation in planning and developing human resources at the Lebak Police Resort, Banten Police, Indonesia.